Question #f3dc0

2 Answers
Oct 16, 2016

1/(sin(x)cos(x)ln(tan(x))

Explanation:

y=ln(ln(tan(x)))

We will use the chain rule as applied to the natural logarithm function:

d/dxln(x)=1/x" "=>" "d/dxln(f(x))=1/f(x)*f'(x)

In the given function we will need to use the chain rule multiple times. The first time will peel away the first ln function:

dy/dx=1/ln(tan(x))*[d/dxln(tan(x))]

Reapplying the chain rule:

dy/dx=1/ln(tan(x)) * [1/tan(x) * d/dxtan(x)]

Since d/dxtan(x)=sec^2(x):

dy/dx=1/ln(tan(x)) * 1/tan(x) * sec^2(x)

Simplifying:

dy/dx=1/ln(tan(x)) * 1/(sin(x)/cos(x)) * 1/cos^2(x)

dy/dx=1/ln(tan(x)) * cos(x)/sin(x) * 1/cos^2(x)

dy/dx=1/(sin(x)cos(x)ln(tan(x))

Oct 17, 2016

1/ ln(tan x) 1/(sin x cos x)

Explanation:

Simpler way for arriving at the result is to let y=ln (ln(tan x), so that it is e^y = ln(tan x)

now differentiate w.r.t x, e^y dy/dx= 1/(tan x) sec^2 x = 1/(sinx cos x)

This gives dy/dx = 1/e^y 1/( sin x cos x)

= 1/ ln(tan x) 1/(sin x cos x)